ISLAMIC EDUCATION POLICY FROM THE OLD ORDER TO THE REFORMATION PERIOD - Moh Takwil (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2024)
This article is a literature study that presents the process of development of Islamic education policies from the Old Order to the Reformation period. It is very important to know the study of policy developments so that it can provide a historical basis for the challenges and developments that have occurred in Islamic education policy. This research is literature, the data collection method is documentary and the analysis is content analysis.The results of this research show that: (1). A significant influence on the development of Islamic educational institutions during the Old Order was the establishment of the Department of Religion based on PP No. 1 of 1946. (2). During the New Order era, efforts were made to integrate religious and general education in 1975 through a decree of 3 Ministers with the implementation of a curriculum in schools consisting of 30% religious lessons and 70% general lessons. Apart from that, it also strengthens the equalization of diplomas from madrasah and school graduates. (3). The reform period was marked by the existence of Law 20 of 2003 which became the foundation for the implementation of religious education for the government and community groups and continued to experience development in its operational field until the birth of Islamic Boarding School Law No. 18 of 2019 which provided recognition and equality for managed Islamic education. boarding school.